Class III treatment with mini-implants anchorage in young adult patients: short and long-term results - Giuliano Bortolo MAINO; Giovanna MAINO; Francesca CREMONINI; Luca LOMBARDO (Dental Press Editora, 2023)
ABSTRACT Introduction: Class III malocclusion should be intercepted and treated at early age, to prevent the necessity of future complex and expensive procedures. The orthopedic facemask therapy has the goal to achieve skeletal changes, minimizing side effects on dentition. The use of skeletal anchorage, combined with Alternate Rapid Maxillary Expansion and Constriction (Alt-RAMEC) protocol, may be effective in treating a greater number of growing Class III patients. Objective: To summarize the existing evidence-based literature on Class III malocclusion treatment in young adult patients, and to illustrate its application and effectiveness, by presenting an emblematic case report. Conclusion: The resolution of the present case, its long-term follow up, along with the studies conducted on a larger sample, demonstrate the effectiveness of the strategic combination of orthopedic and orthodontic treatments by using an hybrid rapid palatal expander and Alt-RAMEC protocol for treating Class III malocclusions in adult patients.